PEMANFAATAN SPARQL INFERENCING NOTATION (SPIN) DALAM PROTOTIPE PENCARIAN DATA RESTORAN BERBASIS SEMANTIK - Haryawan, Cosmas (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Today, more and more information circulating on the internet that cause more difficulty in finding users desired information because many search engine have not used in understanding the concept of semantic search phrase. Application developed in this research is prototype of semantic search on restaurant data using SPARQL Inferencing Notation (SPIN). Search sentence must follow a rule that must be preceded by direction word (tampil, cari, sebut) and followed by a synonym of class which want to find (restoran, makanan, kategori, lokasi). Every search phrase which entered by user will be translated with tokenization process, stemming, stopword removal (filtering process) and followed by the representation of search sentence using keywords in support ontology (words.owl) thus formed run SPARQL to query data located on restaurant.owl ontology. The test result of this research show that the search application which built have an ability to handle wide variety of pattern of question and got the ratio of recall and precision 1:1, thus meaning that this application has a high effectiveness and efficiency in search result.